New Perspectives in Breast Imaging 2017
DOI: 10.5772/intechopen.69726
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Radar Microwave Imaging as an Add-on Modality to Mammography

Abstract: According to global statistics, there is a high incidence of cancer in western countries; and, due to the limited resources available in most health care systems, it seems like one of the most feasible options to fight against cancer might be strict prevention policiessuch as eliminating carcinogens in people's daily lives. Nevertheless, early cancer detection and effective treatment are still necessary, and understanding their efficacy and limitations are important issues that need to be addressed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…In 2019, the team reported that the incorporation of structural priors derived from MRI increased the contrast between tumor and fibroglandular tissue by 59% in permittivity and 192% in conductivity [156]. [157]. The system employed antipodal Vivaldi antennas to overcome the limitations of band-limited Vivaldi antennas and applied Born approximation to reconstruct high quality images.…”
Section: Hybrid Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, the team reported that the incorporation of structural priors derived from MRI increased the contrast between tumor and fibroglandular tissue by 59% in permittivity and 192% in conductivity [156]. [157]. The system employed antipodal Vivaldi antennas to overcome the limitations of band-limited Vivaldi antennas and applied Born approximation to reconstruct high quality images.…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…The system is reported to be ready to move into clinical trials. Near-field MWI has the potential to alleviate the problem of low contrast faced at X-ray frequencies as tissues show more contrast at microwave frequencies [157].…”
Section: Hybrid Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the preliminary results of the NRIMS working in a standalone mode are presented for the sake of assessing its independent performance in a simple experiment. In the proceeding subsections, each part of the NRIMS is described [ 117 , 118 ].…”
Section: A Bimodal System: Dbt Plus Nrimentioning
confidence: 99%
“…Unfortunately, standalone MWI systems typically struggle to accurately detect cancerous lesions due to the heterogeneous distribution of tissues within the breast. Analyses of existing MWI breast cancer detection methods can be found in [4,5].…”
Section: Introductionmentioning
confidence: 99%